Wyznacz pierwiastki wielomianu w a następnie rozwiąż nierówność -x4+2x3-4x2+8x.

Odpowiedź :

Odpowiedź:

-x⁴+2x³-4x²+8x = -x(x³-2x²+4x-8)=-x * x²(x-2) +4(x-2)= -x(x²+4)(x-2)

pierwiastki : x1= 0                 x2= 2

w(x) > 0  dla   x∈(0,2)                w(x)< 0  dla x ∈(-∞,0) lub  (2,+∞)

Szczegółowe wyjaśnienie:

[tex]-x^4+2x^3-4x^2+8x=0\\-x^3(x-2)-4x(x-2)=0\\(-x^3-4x)(x-2)=0\\-x(x^2+4)(x-2)=0\\\\-x=0\\x=0\\\\x^2+4=0\\x^2\neq-4\\\\x-2=0\\x=2\\\\\text{Pierwiastki wielomianu: } x=0, x=2[/tex]